Venanzio Rauzzini and the birth of a new style in English singing : scandalous lessons - Robertson-Kirkland, Brianna E., 1989- (New York : Routledge, 2021)
"Since the eighteenth century, the one-to-one singing lesson has been the most common method of delivery. The scenario allows the teacher to familiarize and individualize the lesson to suit the needs of their student; however, it can also lead to speculation about what is taught. More troubling is the heightened risk of gossip and rumor with the private space generating speculation about the student-teacher relationship. Venanzio Rauzzini (1746-1810), an Italian castrato living in England who became a highly sought-after singing master, was particularly susceptible since his students tended to be women, whose moral character was under more scrutiny than their male counterparts. Even so in 1792, The Bath Chronicle proclaimed the Italian castrato: "the father of a new style in English singing." Branding Rauzzini as a founder of an English style was not an error, but indicative of deep-seeded anxieties about the Italian invasion on England's musical culture. This book places teaching at the center of the socio-historical narrative and provides unique insight into musical culture. Using a microhistory approach, this study is the first to focus in on the impact of teaching and casts new light on issues of celebrity culture, gender and nationalism in Georgian England"--
Prelude. "The First Master for Singing in the Universe" -- Britain's Music Education in Decline -- Using and Creating Celebrity -- Natural or Learned? -- "The Father of a New Style in English Singing"? -- A Master's Treatise. A Legacy Product -- Master or Servant. Vilifying the Female Amateur and the Italian Master -- A Respectable Master or a Scandalous Lover? -- Postlude. The Eighteenth Century in the Twenty-First Century -- Appendix 1. Anna Selina (Nancy) Storace's Performances Between 1773-1778 -- Appendix 2. Singers Advertised as "Pupils of Rauzzini".
Keywords: Rauzzini, Venanzio, -- 1746-1810.; Singing -- Instruction and study -- Great Britain -- History -- 18th century; Teacher-student relationships -- Great Britain -- History -- 18th century; Music -- Social aspects -- Great Britain -- History -- 18th century; Voice teachers; Castrati; England -- Social life and customs -- 18th century; HISTORY / Europe / General; HISTORY / Europe / Great Britain; HISTORY / Modern / 18th Century